The Role of Japan and other Northeast Asian economies in ASEAN - Daquila, Teofilo C (Research Institute for Comparative Literature and Cross-Cultural Studies, University of Alberta, 2014)
East Asian cultural and historical perspectives : histories and society/culture and literatures